New Method to Estimate Central Systolic Blood Pressure From Peripheral Pressure: A Proof of Concept and Validation Study - Chemla, Denis; Millasseau, Sandrine; Hamzaoui, Olfa; Teboul, Jean-Louis; Monnet, Xavier; Michard, Frédéric; Jozwiak, Mathieu (Frontiers in Cardiovascular Medicine, 2021)
Objective: The non-invasive estimation of central systolic blood pressure (cSBP) is increasingly performed using new devices based on various pulse acquisition techniques and mathematical analyses. These devices are most often calibrated assuming that mean (MBP) and diastolic (DBP) BP are essentially unchanged when pressure wave travels from aorta to peripheral artery, an assumption which is evidence-based. We tested a new empirical formula for the Direct Central Blood Pressure estimation of cSBP using MBP and DBP only (DCBP=MBP²/DBP). Methods and Results: First, we performed a post-hoc analysis of our prospective invasive high-fidelity aortic pressure database (n=139, age 49±12 years, 78% males). The cSBP was 146.0±31.1 mmHg. The error between aortic DCBP and cSBP was -0.9±7.4mmHg, and there was no bias across the cSBP range (82.5-204.0mmHg). Second, we analyzed 64 patients from two studies of the literature in whom invasive high-fidelity pressures were simultaneously obtained in the aorta and brachial artery. The weighed mean error between brachial DCBP and cSBP was 1.1mmHg. Finally, 30 intensive care unit patients equipped with fluid-filled catheter in the radial artery were prospectively studied. The cSBP (115.7±18.2mmHg) was estimated by carotid tonometry. The error between radial DCBP and cSBP was -0.4±5.8mmHg and there was no bias across the range. Conclusion: Our study shows that cSBP could be reliably estimated from MBP and DBP only, providing BP measurement errors are minimized. DCBP may have implications for assessing cardiovascular risk associated to cSBP on large BP databases, a point that deserves further studies.